MERGERS AND ACQUISITIONS IN INDIA - Agarwal, Ankita (2009)
From the past few decades, Mergers and Acquisitions (M&A) have dominated the environment in which the companies operate. Whenever there is an announcement about a merger, there is an excitement and expectation among the shareholders. This expectation may or may not convert into an abnormal return. It is useful to have some kind of research activity on the performance of M&A, as both bidders and target firms will gain from it. The results have revealed that on average, the returns to the target companies are positive and that they gain from mergers. However, the bidder returns may be zero or negative, but it turns out be a different story in the long run. My dissertation identifies the performance of 86 Mergers and Acquisitions in India and the primary objective for this study will be to examine the change in firms share prices and the impact of mergers and acquisition on the returns to the shareholders of both bidder and target firms surrounding the announcement days. It then attempts to verify the significance of the same in the short-term. Whether the abnormal returns are significant to the announcement of the merger, determines the success of the merger in the shortterm. The research also estimates the beta coefficient for 86 bidder and target firms, during the announcement period (10 days before the announcement day and 19 days after the announcement days) and before the announcement period (ranging from150 days to 11 days before announcement). I have also shown some statistical test to see if the changes in the beta coefficient and required returns are significant or not Further, the research is based on types of mergers factor (Horizontal and non-horizontal) which might be closely related and give different returns to the target shareholders and bidder shareholders on the days surrounding the announcement. The event study methodology has been employed to assess the performance of both bidder and target firms surrounding the announcement days. The results of the event study reveal that on an average, the bidder companies experience a negative cumulative average abnormal returns (CAAR) of -1.03% and the target companies experience a positive CAAR of 12.074%